PERKEMBANGAN STUDI ISLAM DI INDONESIA - Dini Marshanda; Uray Alkaf (Adisam Publisher, 2025)
This paper discusses the development of Islamic studies in Indonesia. At the end of the 19th century, the development of Islamic education in Indonesia began with the birth of Dutch-style schools: European schools, Vernahuler schools. The European school was specialized for Dutch nobles and the Vernahuler school was specialized for Dutch citizens. In addition, there were indigenous schools that had the same system as these Dutch schools, such as Taman Siswa schools. Then in the second decade of the 20th century, madrassas and Dutch-style schools were established by Islamic organizations such as Muhammadiyah, NU, Jama'at al-Khair, and others. The method used in this research is a literature study using a qualitative approach. The analysis used to analyze the data is theoretical analysis. The results showed that the development of Islamic studies is growing marked by the establishment of Islamic universities cannot be separated from the desire of Indonesian Muslims to have Islamic higher education institutions since colonial times. In April 1945, a meeting was held between various leaders of Islamic organizations, ulama, and scholars. After sufficient preparation, on July 8, 1945 or on 27 Rajab 1364 H coinciding with Isra Mi'raj, the official opening of the Islamic Higher School (STI) was held in Jakarta. From here we now recognize UII, IAIN, UIN, STAIN and so on.